Confined-range light-operated anti-tumor composite hydrogel drug reservoir as well as preparation method and application of confined-range light-operated anti-tumor composite hydrogel drug reservoir

By combining photothermal nanoparticles with drug-loadable temperature-sensitive hydrogels, a limited-domain photocontrol drug reservoir was constructed, which solved the problems of poor targeting and poor temporal and spatial controllability in the existing technology, and achieved efficient and accurate tumor treatment effects .

CN119405592APending Publication Date: 2025-02-11ZHIYUAN BAIMAI (ZHEJIANG) TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411805884.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing tumor treatment technologies have poor targeting, poor temporal and spatial controllability, and the photothermal effect in photo-assisted treatment, making it difficult to achieve accurate and personalized tumor treatment.

Method used

By combining photothermal nanoparticles with drug-loadable temperature-sensitive hydrogels, a limited-domain photocontrol drug reservoir is built, and the photothermal effect is used to regulate drug release kinetics to achieve time-space controllable anti-tumor drug delivery.

Benefits of technology

It achieves high local concentration of drugs, avoids systemic toxicity, reduces the side effects of photothermal effects, and achieves a space-controllable tumor treatment effect through non-invasive methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119405592A_ABST
    Figure CN119405592A_ABST
Patent Text Reader

Abstract

The invention discloses a range-limited light-operated anti-tumor composite hydrogel drug reservoir and a preparation method and application thereof.The light-responsive drug-loaded nano hydrogel is loaded into a temperature-sensitive hydrogel system to form the range-limited hydrogel drug reservoir with light-operated drug release, the preparation method comprises the steps that PEG, LA and GA are added into a three-necked flask for an oil bath reaction, and the temperature-sensitive hydrogel system is obtained; after the reaction, purifying and freeze-drying to obtain a PLGA-PEG-PLGA block copolymer; the PLGA-PEG-PLGA segmented copolymer is dissolved in ultrapure water, and a PLGA-PEG-PLGA sol is obtained; and dissolving the drug-loaded PDA (at) P (NIPAAm-co-AM) nano hydrogel into the PLGA-PEG-PLGA sol, so as to obtain the confined light-operated anti-tumor composite hydrogel drug reservoir. The confined light-operated anti-tumor composite hydrogel drug reservoir has light-responsive drug delivery performance, not only has space-time controllability of drug release, but also weakens the problems of photothermal effect and the like in light-assisted therapy, so that accurate tumor therapy can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biological hydrogel materials, and in particular relates to a localized light-controlled anti-tumor composite hydrogel drug reservoir and a preparation method and application thereof. Background Art

[0002] According to the latest release of the World Health Organization in 2024, as the world's primary disease burden, cancer has led to an increasingly high mortality rate worldwide. In 2022, the number of cancer deaths reached 9.7 million, and cancer treatment is still a challenge facing the world. Traditional tumor treatment methods, including surgical treatment, systemic treatment, radiotherapy, etc., still have the following shortcomings in clinical practice: in terms of drug administration, poor targeting, low patient comfort and poor compliance; in terms of drug administration effect, drug diffusion is prone to occur, causing systemic toxicity; in terms of treatment effect, the prognosis is poor, and tumor cell metastasis, tumor recurrence and other problems often occur. As an emerging preparation, hydrogel has great advantages in tumor treatment. Most hydrogel materials have injectable properties, which can achieve precise lesion area drug administration effects; secondly, in the process of peritumoral or intratumoral injection of hydrogel materials, the drug can fully infiltrate the tumor tissue, and while being highly effective in anti-tumor, it can also establish a barrier between tumor tissue and normal tissue, reducing or even avoiding tumor cell metastasis; as a material with high water content and high biocompatibility, hydrogel can be fixed in tumor tissue as a drug reservoir to achieve the purpose of long-term treatment. However, hydrogel drug delivery mainly relies on the passive diffusion of drugs, so the controllability of drug release and therapeutic effects is weak, making it difficult to achieve precise personalized treatment.

[0003] Therefore, in view of the shortcomings of hydrogel materials in tumor treatment and drug delivery, it is urgent to develop new confined and controllable anti-tumor hydrogel materials to achieve precise and spatiotemporally controllable treatment methods. Summary of the invention

[0004] The purpose of the present invention is to provide a confined light-controlled anti-tumor composite hydrogel drug reservoir and its preparation method and application in order to solve the problems existing in the related technology, such as poor targeting, poor spatiotemporal controllability, and photothermal effect in light-assisted therapy.

[0005] The present invention constructs a confined light-controlled drug reservoir based on photothermal nanoparticles and drug-loaded thermosensitive hydrogels, combines the drug-loaded nanoparticles with an injectable hydrogel matrix to maintain the local effective drug concentration and avoid systemic drug circulation; at the same time, the heat energy generated by the photothermal nanoparticles under illumination is used to affect the phase change behavior of the drug-loaded thermosensitive hydrogel, thereby regulating the drug release kinetics of the drug reservoir, and ultimately achieving time-space controllable anti-tumor drug delivery.

[0006] One of the technical solutions of the present invention is to provide a confined light-controlled anti-tumor composite hydrogel drug reservoir.

[0007] The composite hydrogel drug reservoir is composed of PLGA-PEG-PLGA sol and DOX-loaded PDA@P(NIPAAm-co-AM) nanohydrogel; the PLGA-PEG-PLGA sol and the DOX-loaded PDA@P(NIPAAm-co-AM) nanohydrogel are respectively prepared by dissolving PLGA-PEG-PLGA block copolymer and DOX-loaded PDA@P(NIPAAm-co-AM) nanogel in water, wherein the mass ratio of PLGA-PEG-PLGA block copolymer to DOX-loaded PDA@P(NIPAAm-co-AM) nanogel is (5-20):1; wherein the mass ratio of DOX to PDA@P(NIPAAm-co-AM) is 1:(1-100); and the molar ratio of NIPAAm to AM in the DOX-loaded PDA@P(NIPAAm-co-AM) is 6:1.

[0008] The composite hydrogel drug reservoir is in a solution state at room temperature and can be locally injected into or around a tumor lesion via a syringe. After injection, it will solidify from a liquid state into a gel-state confined drug reservoir under the action of body temperature. In the gel state, the drug can be slowly released through the slow dissolution of the gel itself. In addition, the drug reservoir can realize sensitive light-controlled drug release. Based on the photothermal conversion characteristics and temperature-sensitive characteristics, PDA nanoparticles can realize photothermal energy conversion under laser irradiation, absorb light energy and convert it into heat, increase the local temperature, further increase the gel temperature, collapse and dehydrate the gel structure, accelerate the drug outflow and diffusion rate, get rid of the rate limitation of passive diffusion of drug molecules, and realize more precise and controllable personalized tumor treatment. The aqueous solution of PLGA-PEG-PLGA block copolymer has two phase transition temperatures. When the temperature is lower than the lower critical phase transition temperature (LCST), the PLGA-PEG-PLGA block copolymer is in a dispersed and flowable sol state in the aqueous solution; when the temperature is higher than the upper critical phase transition temperature (UCST), the PLGA-PEG-PLGA block copolymer collapses and precipitates in the aqueous solution to achieve phase separation; and when the temperature is between LCST and UCST, the PLGA-PEG-PLGA sol is transformed into a non-flowing gel state, which is a thermosensitive hydrogel.

[0009] The second technical solution of the present invention is to provide a method for preparing a confined light-controlled anti-tumor composite hydrogel drug reservoir, which comprises the following steps: dissolving a PLGA-PEG-PLGA block copolymer in ultrapure water to obtain a PLGA-PEG-PLGA sol; dissolving a DOX-loaded PDA@P (NIPAAm-co-AM) nanohydrogel in the PLGA-PEG-PLGA sol to obtain a confined light-controlled anti-tumor composite hydrogel drug reservoir.

[0010] Wherein, the PLGA-PEG-PLGA block copolymer is prepared by the following method: (1) PEG, LA and GA are mixed, heated in an oil bath to 100-120° C., and stirred for 0.5-2 hours in a vacuum state to obtain a polymer fluid; the ratio of the mass of PEG to the total mass of LA and GA monomers is 1:(2-3); wherein the mass ratio of LA to GA is (3-4):1; (2) Tributyltin butenedioate C 16 H 30 O4Sn is added dropwise to the polymer fluid, heated to 120-150°C in an oil bath, reacted for 6-24 hours under nitrogen protection, purified and freeze-dried after the reaction to obtain a PLGA-PEG-PLGA block copolymer; the C 16 H 30 The mass ratio of O4Sn to polymer mass is 0.1-0.5%; The PEG is PEG 1500 or PEG 1500 and PEG 1000 in a mass ratio of (1-2):1. PEG is a hydrophilic segment in the block copolymer. If the average molecular weight of PEG is too small, the hydrophilicity of the synthesized PLGA-PEG-PLGA block copolymer will be reduced, making it unable to dissolve in a low-temperature aqueous solution. If the average molecular weight of PEG is too large, the block copolymer will be too hydrophilic, requiring an excessively high temperature to dehydrate the polymer segments, and it will be impossible to induce a phase transition of PLGA-PEG-PLGA within a controllable temperature range.

[0011] At low temperatures, the hydrophilic PEG segments in the PLGA-PEG-PLGA block copolymer allow the entire copolymer to dissolve in water, forming a free-flowing solution state. As the temperature rises, the hydrogen bonding force between PEG and water molecules weakens, and the hydrophobic PLGA segments dominate the rearrangement of the copolymer molecular chains to form micelles.

[0012] When the temperature is higher than the lower critical phase transition temperature (LCST), the hydrophobic interaction between micelles is enhanced, and the micelles aggregate in water to form a three-dimensional network gel structure. When the temperature is higher than the upper critical phase transition temperature (UCST), the hydrophobicity of the chain segments further increases, which dominates the dehydration of the micelles, and the gel structure collapses and separates from the water phase. As the mass ratio of PEG 1500 to PEG 1000 decreases, the range between the LCST and UCST of the PLGA-PEG-PLGA block copolymer gradually increases, that is, the LCST of the PLGA-PEG-PLGA block copolymer gradually decreases, and the UCST gradually increases.

[0013] Furthermore, the method of preparing the DOX-loaded PDA@P(NIPAAm-co-AM) nanohydrogel is as follows: (1) Add NIPAAm (N-isopropylacrylamide) and AM (acrylamide) to water, stir and evacuate to obtain an aqueous solution of NIPAAm and AM; (2) Add 40 parts by volume of ethanol to 90 parts by volume of ultrapure water, stir evenly at 35°C-40°C, then immediately add 3 parts by volume of ammonia water and stir evenly, add dopamine hydrochloride aqueous solution, wherein the mass volume ratio of dopamine hydrochloride to ethanol is 50 mg:4 ml, stir at 35°C-40°C and protect from light, centrifuge and wash to obtain PDA nanoparticles, and disperse the PDA nanoparticles in water to obtain a PDA solution; (3) PDA (polydopamine) solution, NIPAAm and AM aqueous solution, SBS (sodium metabisulfite), APS (ammonium persulfate), BIS (methyl acrylamide), and SDS (sodium dodecyl sulfate) were mixed for reaction, and then dialyzed and freeze-dried to obtain PDA@P(NIPAAm-co-AM) nanogel; wherein the mass ratio of PDA, NIPAAm, AM, APS, SBS, SDS, and BIS was 1:180:30:2:2:40:5; (4) Dissolve the PDA@P(NIPAAm-co-AM) nanogel in an aqueous solution of DOX to obtain DOX-loaded PDA@P(NIPAAm-co-AM) nanohydrogel.

[0014] The third technical solution of the present invention is to provide an application of a confined light-controlled anti-tumor composite hydrogel drug reservoir prepared by the above method in the preparation of a confined light-controlled anti-tumor preparation.

[0015] Beneficial effects of the present invention: The present invention combines drug-loaded PDA@P (NIPAAm-co-AM) nanohydrogel with photothermal response performance with injectable thermosensitive hydrogel to form a confined light-controlled anti-tumor composite hydrogel drug reservoir. Cell experiments and animal experiments have shown that the drug reservoir has good drug confined storage and external field controlled release performance, reduces the side effects of photothermal effect during treatment, and achieves a tumor treatment effect that is controllable in time and space in a non-invasive manner.

[0016] The preparation method of the invention is simple, the performance of the light-confined light-controlled anti-tumor composite hydrogel drug reservoir is stable, and it has considerable clinical application value and broad application conversion prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 The spectra of the PLGA-PEG-PLGA block copolymers of Examples 1-4, (a) is the FTIR spectrum, (b) is 13 C-NMR spectrum, (c) 1 H-NMR spectrum; Figure 2is a phase transition temperature diagram of the PLGA-PEG-PLGA block copolymer of Examples 1-4; Figure 3 is the rheological curve of the PLGA-PEG-PLGA block copolymer of Examples 1-4; Figure 4 is the degradation curve of the PLGA-PEG-PLGA block copolymer of Examples 1-4; Figure 5 The drug release curve of the composite hydrogel drug reservoir of Example 1-3; Figure 6 The photothermal temperature rise curves of PDA@P(NIPAAm-co-AM) nanohydrogels with different concentrations in Example 2; Figure 7 is the drug release curve of DPNP ⅠNP in Example 1; Figure 8 The cytotoxicity graph of different materials in Example 1 after 24 hours of culture; Fig. 9 This is the cytotoxicity graph of DPNP I / 10 after 24h of culture in Example 1; Fig.10 The cytotoxicity diagrams of different groups in Example 1; Fig.11 This is the curve of tumor volume change over time after 21 days of treatment; Fig.12 The figure is a graph of tumor inhibition rate after 21 days of treatment; NIR represents applied light; PNP represents a composite hydrogel containing the same PDA@P (NIPAAm-co-AM) nanohydrogel concentration as the confined light-controlled anti-tumor composite hydrogel drug reservoir, but without DOX; DPN represents a drug-loaded PDA@P (NIPAAm-co-AM) nanohydrogel with the same DOX and PDA@P (NIPAAm-co-AM) nanohydrogel content as the confined light-controlled anti-tumor composite hydrogel drug reservoir, but without PLGA-PEG-PLGA Ⅱ sol. DETAILED DESCRIPTION

[0018] The following examples are used to further illustrate the present invention, and their purpose is to illustrate the present invention and should not be construed as limiting the scope of the present invention. Unless otherwise specified, all parts by weight and weight percentages are used below.

[0019] The raw materials used in the present invention, unless otherwise specified, are conventional commercially available products; the methods used in the present invention, unless otherwise specified, are conventional methods in the art.

[0020] The embodiments of the present invention are further described below with reference to a plurality of embodiments.

[0021] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0022] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0023] Example 1 (1) The preparation method of PLGA-PEG-PLGA Ⅰ sol is as follows: In step (1.1), 6 g PEG 1500, 9 g LA and 3 g GA were weighed, heated in an oil bath at 100 °C, and stirred under vacuum for 2 h to obtain a mixed polymer fluid.

[0024] Step (1.2), pipette 18 mg of C 16 H 30 O4Sn was added dropwise to the polymer fluid, heated in an oil bath at 150°C, stirred, and reacted for 6 h under nitrogen protection. After the reaction, the polymer was purified and freeze-dried to finally obtain a PLGA-PEG-PLGA block copolymer.

[0025] In step (1.3), the PLGA-PEG-PLGA block copolymer was weighed and dissolved in ultrapure water according to the mass concentration to obtain a series of PLGA-PEG-PLGA sols of mass concentrations, including 10 wt%, 15 wt%, 20 wt%, 25 wt%, and 30 wt%. The obtained PLGA-PEG-PLGA block copolymer was named PLGA-PEG-PLGA Ⅰ.

[0026] The block copolymer was dissolved in ultrapure water to form a sol with a mass concentration of 20 wt%.

[0027] (2) The preparation process of DOX-loaded PDA@P(NIPAAm-co-AM) nanohydrogel is as follows: (2.1) Add 360 mg NIPAAm and 60 mg AM to water, stir and evacuate to obtain an aqueous solution of NIPAAm and AM; (2.2) Add 40 parts by volume of ethanol to 90 parts by volume of ultrapure water, stir evenly at 35°C, then immediately add 3 parts by volume of NH3 in ultrapure water and stir evenly, add dopamine hydrochloride aqueous solution, wherein the mass volume ratio of dopamine hydrochloride to ethanol is 50 mg:4 ml, stir at 35°C and protect from light, centrifuge and wash to obtain PDA nanoparticles, and disperse the PDA nanoparticles in water to obtain a PDA solution; (2.3) 2 mg of PDA nanoparticles aqueous solution, NIPAAm and AM aqueous solution, 4 mg of SBS, 4 mg of APS, 10 mg of BIS, and 80 mg of SDS were mixed for reaction, and then dialyzed and freeze-dried to obtain PDA@P(NIPAAm-co-AM) nanogel; (2.4) Dissolve the PDA@P(NIPAAm-co-AM) nanogel in an aqueous solution of DOX to obtain DOX-loaded PDA@P(NIPAAm-co-AM) nanohydrogel.

[0028] The concentration of the DOX aqueous solution in step 2.4 was adjusted to obtain hydrogels with different drug loading concentrations, including the mass ratios of DOX to PDA@P(NIPAAm-co-AM) nanogels of 1:1, 1:10, and 1:100.

[0029] (3) Composite The PLGA-PEG-PLGA sol obtained in step 1 and the drug-loaded PDA@P (NIPAAm-co-AM) nanohydrogel with different drug loading concentrations obtained in step 2 are combined in a mass ratio of PLGA-PEG-PLGA block copolymer to PDA@P (NIPAAm-co-AM) nanogel of 5:1 to form a composite sol. After the composite sol is heated and undergoes a phase transition, a confined composite drug reservoir is formed.

[0030] Among them, the drug reservoir obtained by compounding the drug-loaded PDA@P(NIPAAm-co-AM) nanohydrogel with a mass ratio of DOX to PDA@P(NIPAAm-co-AM) nanogel of 1:1 with PLGA-PEG-PLGA sol was labeled as DPNP Ⅰ / 1.

[0031] The drug reservoir obtained by compounding the drug-loaded PDA@P(NIPAAm-co-AM) nanohydrogel with a mass ratio of DOX to PDA@P(NIPAAm-co-AM) nanogel of 1:10 with PLGA-PEG-PLGA sol was labeled as DPNP Ⅰ / 10.

[0032] The drug reservoir obtained by compounding the drug-loaded PDA@P(NIPAAm-co-AM) nanohydrogel with a mass ratio of DOX to PDA@P(NIPAAm-co-AM) nanogel of 1:100 with PLGA-PEG-PLGA sol was labeled as DPNP I / 100.

[0033] The anti-tumor performance of the confined light-controlled anti-tumor composite hydrogel drug reservoir was verified from the killing effect at the cellular level. The cells used in the experiment were mouse breast cancer cells (4T1). The confined light-controlled anti-tumor composite hydrogel drug reservoir was co-cultured with 4T1 cells for 24 h. During the culture process, the illumination group was irradiated with 2 W of light for 5 min, and the wavelength of the light was 808 nm.

[0034] Figure 8 The survival rate of cells after co-culture is shown in the figure, and DPNP I / 1, DPNP I / 10, and DPNP I / 100 are abbreviated as I / 1, I / 10, and I / 100, respectively. It can be seen from the figure that the same material can enhance the killing of 4T1 by applying light, but in the DPNP irradiation group, when the concentration of DOX reaches 15 μg / mL, the light will strongly kill 4T1 cells, while the DPNP Ⅰ / 1 irradiation group is compared with the non-irradiation group, and the killing effect of applying light on 4T1 is not obvious. Therefore, DPNP Ⅰ / 10 is preferably used as the confined light-controlled anti-tumor composite hydrogel drug reservoir used in the following examples.

[0035] By comparing the killing effects of different groups on 4T1 cells, the photostimulated chemotherapeutic performance of the confined light-controlled anti-tumor composite hydrogel drug reservoir DPNP Ⅰ / 10 was verified.

[0036] 4T1 cells were co-cultured with the confined light-controlled anti-tumor composite hydrogel drug reservoir DPNP Ⅰ / 10 for 24 h to verify the anti-tumor properties of the material. Fig. 9 As shown. In the NIR*1 group, light was applied once for 5 min during the culture process; in the NIR*2 group, light was applied twice during the culture process, with an interval of 3 h and each time for 5 min. The light conditions were 808 nm near-infrared light with a power of 2 W. Applying light twice can significantly kill 4T1 cells.

[0037] The killing effects of five groups of materials on 4T1 cells were compared, including the confined light-controlled anti-tumor composite hydrogel drug reservoir DPNP I / 10 group with a DOX concentration of 15 μg / mL, the group irradiated with light once, the group irradiated with light twice, and the composite hydrogel group irradiated with light twice (under the condition of DOX concentration of 15 μg / mL, the composite hydrogel with a mass ratio of 1 / 10 of the PDA@P(NIPAAm-co-AM) nanohydrogel concentration and the composite hydrogel with a mass ratio of 1 / 100 of the PDA@P(NIPAAm-co-AM) nanohydrogel concentration). Fig.10 As shown, the significant tumor cell killing effect of the confined light-controlled anti-tumor composite hydrogel drug reservoir DPNP Ⅰ / 10 after two illuminations comes from the chemotherapy drug DOX, rather than the photothermal effect produced by the confined light-controlled anti-tumor composite hydrogel drug reservoir DPNP Ⅰ / 10. From the cellular level, it shows that the confined light-controlled anti-tumor composite hydrogel drug reservoir DPNP Ⅰ / 10 has excellent light-controlled anti-tumor performance.

[0038] Example 2 The difference from Example 1 is that in step (1) of Example 2, 4 g of PEG 1500 and 2 g of PEG 1000 are weighed, and the obtained PLGA-PEG-PLGA block copolymer is named PLGA-PEG-PLGA II. Finally, a confined composite drug reservoir (DPNP II) is formed.

[0039] Example 3 The difference from Example 1 is that in step (1) of Example 3, 3.6 g of PEG 1500 and 2.4 g of PEG 1000 were weighed, and the obtained PLGA-PEG-PLGA block copolymer was named PLGA-PEG-PLGA III. Finally, a confined composite drug reservoir (DPNP III) was formed.

[0040] Example 4 The difference from Example 1 is that in step (1) of Example 2, 3 g of PEG 1500 and 3 g of PEG 1000 were weighed, and the obtained PLGA-PEG-PLGA block copolymer was named PLGA-PEG-PLGA IV.

[0041] Figure 1 The spectra of PLGA-PEG-PLGA block copolymers with different mass ratios of PEG 1500 and PEG 1000 in the present invention are as follows: (a) is the FTIR spectrum, (b) is the 13C-NMR spectrum, and (c) is the 1H-NMR spectrum. The successful synthesis of the PLGA-PEG-PLGA block copolymers is verified by the overlapping characteristic peaks in each spectrum.

[0042] Example 5 (1) Weigh 6 g of PEG 1500, place it in a three-necked flask, heat it in an oil bath at 150°C, and evacuate the flask for 2 h while stirring to obtain a PEG fluid.

[0043] (2) The PEG fluid was cooled to room temperature, and then 14.4 g of LA and 3.6 g of GA were added. The mixture was heated in an oil bath at 120 °C and vacuumed for 30 min with stirring to obtain a mixed polymer fluid.

[0044] (3) Absorb 90 mg of C 16 H 30 O4Sn was added dropwise to the polymer fluid, heated in an oil bath at 120°C, stirred, and reacted under nitrogen protection for 24 h. After the reaction, the mixture was purified and freeze-dried to finally obtain a PLGA-PEG-PLGA block copolymer. The block copolymer was dissolved in ultrapure water to form a sol with a mass concentration of 20 wt%.

[0045] (4) Add 360 mg NIPAAm and 60 mg AM to water, stir and evacuate to obtain an aqueous solution of NIPAAm and AM; (5) Add 40 parts by volume of ethanol to 90 parts by volume of ultrapure water, stir evenly at 40°C, immediately add 3 parts by volume of ammonia water and stir evenly, add dopamine hydrochloride aqueous solution, wherein the mass volume ratio of dopamine hydrochloride to ethanol is 50 mg:4 ml, stir at 40°C and protect from light, obtain PDA nanoparticles after centrifugation and washing, and disperse the PDA nanoparticles in water to obtain a PDA solution; (6) 2 mg of PDA nanoparticles aqueous solution, NIPAAm and AM aqueous solution, 4 mg of SBS, 4 mg of APS, 10 mg of BIS, and 80 mg of SDS were mixed for reaction, and then dialyzed and freeze-dried to obtain PDA@P(NIPAAm-co-AM) nanogel; (7) The PDA@P(NIPAAm-co-AM) nanogel was dissolved in an aqueous solution of DOX to obtain DOX-loaded PDA@P(NIPAAm-co-AM) nanohydrogel. The mass ratio of DOX to PDA@P(NIPAAm-co-AM) nanogel was 1:10.

[0046] The PLGA-PEG-PLGA sol and the above-mentioned drug-loaded PDA@P (NIPAAm-co-AM) nanohydrogel were combined in a mass ratio of 20:1 between the PLGA-PEG-PLGA block copolymer and the PDA@P (NIPAAm-co-AM) nanogel to form a composite sol. After the composite sol was heated and a phase transition occurred, a confined composite drug reservoir was formed.

[0047] Example 6 The phase transition temperatures of the PLGA-PEG-PLGA block copolymers of different mass concentrations in Examples 1-4 were determined by the inversion method. Figure 2 As shown in the figure, PLGA-PEG-PLGA block copolymer has two phase transition temperatures. When the temperature is lower than the lower critical phase transition temperature (LCST), the aqueous solution of PLGA-PEG-PLGA block copolymer is in a flowing sol state; when the temperature is higher than the upper critical phase transition temperature (UCST), PLGA-PEG-PLGA block copolymer collapses and precipitates in the aqueous solution to achieve phase separation; and when the temperature is between LCST and UCST, PLGA-PEG-PLGA sol turns into a non-flowing gel state, that is, a thermosensitive hydrogel. In addition, as the mass ratio of PEG 1500 to PEG 1000 decreases, the range between LCST and UCST of PLGA-PEG-PLGA block copolymer gradually increases, that is, the LCST of PLGA-PEG-PLGA block copolymer gradually decreases, and the UCST gradually increases.

[0048] Figure 3 The PLGA-PEG-PLGA sol with a mass concentration of 20 wt% in Examples 1-4 was selected for rheological testing, and the change in modulus with temperature was measured at a strain of 1% and a frequency of 1 Hz. (a) is PLGA-PEG-PLGA Ⅰ, (b) is PLGA-PEG-PLGA Ⅱ, (c) is PLGA-PEG-PLGA Ⅲ, and (d) is PLGA-PEG-PLGA Ⅳ. The LCST of the PLGA-PEG-PLGA sol was inferred by the intersection of the storage modulus (G') and the loss modulus (G"), and the rheological test results were consistent with the inversion experiment results.

[0049] In order to verify the degradation performance of the PLGA-PEG-PLGA block copolymers in Examples 1-4, 0.5 mL of 20 wt% block copolymer sol was taken in a 10 mL centrifuge tube, and 3 mL of PBS solution was slowly added after the thermosensitive hydrogel was formed at 37°C. The mass of the thermosensitive hydrogel was measured at 37°C and a rotation speed of 50 rpm, and the mass change curve over time was plotted to obtain the degradation curves of four thermosensitive hydrogels with a mass concentration of 20 wt%.

[0050] like Figure 4As shown, the block copolymers in Examples 1-4 are abbreviated as Ⅰ, Ⅱ, Ⅲ, and Ⅳ, respectively. As the mass ratio of PEG 1500 to PEG 1000 decreases, the degradation period of the thermosensitive hydrogel with a mass concentration of 20 wt% becomes longer. The degradation period of the thermosensitive hydrogel with a mass concentration of 20 wt% formed by the PLGA-PEG-PLGAⅡ block copolymer is about 25 days, while the degradation period of the thermosensitive hydrogel with a mass concentration of 20 wt% formed by the PLGA-PEG-PLGAⅣ block copolymer exceeds 40 days.

[0051] In order to evaluate the drug release performance of the composite drug reservoirs of Examples 1-3, 2 mL of composite sols were taken respectively, wherein the concentration of DOX was 1 mg / mL, and the composite sols were placed in 10 mL centrifuge tubes. Phase transition occurred at 37°C to form composite drug reservoirs, and 3 mL of PBS solution was slowly added as the release medium. At 37°C and 45°C, 50 rpm, 2 mL of the release medium was drawn at specific times, and the release amount of DOX was measured by UV-vis spectrophotometer, and 2 mL of blank PBS solution was supplemented at the same time.

[0052] Figure 5 The drug release curves of the three composite drug reservoirs are shown in the mathematical model calculation. The three composite drug reservoirs all show the controlled release of the drug delivery system of the erosion-type carrier. Among them, DPNP I and DPNP II release the drug DOX by the combined action of thermosensitive hydrogel erosion and drug diffusion at 37°C, while the drug release is achieved by drug diffusion alone at 45°C.

[0053] Table 1 Drug release model fitting of composite drug reservoir

[0054] In order to verify the effect of photothermal generated by PDA@P (NIPAAm-co-AM) nanohydrogel under laser irradiation on the temperature rise of DPNPⅡ, the temperature rise curves of composite hydrogels containing different concentrations of PDA@P (NIPAAm-co-AM) nanohydrogel were measured.

[0055] Specifically, a series of concentrations of PDA@P(NIPAAm-co-AM) nanohydrogels were dissolved in PLGA-PEG-PLGA sol with a mass concentration of 20 wt% to obtain composite hydrogels, including 0 μg / mL, 50 μg / mL, 100 μg / mL, 150 μg / mL, 200 μg / mL, 250 μg / mL, and 300 μg / mL. The near-infrared light with a wavelength of 808 nm was irradiated for 6 min at a power of 2 W, and the temperature rise curves of each concentration were measured by a FLIR infrared thermal imager, as shown in FIG. Figure 6As shown, the temperature of the composite hydrogel with a PDA@P(NIPAAm-co-AM) nanohydrogel concentration of 150 μg / mL reached 40.4°C after 5 min of illumination. When the concentration was as high as 200 μg / mL, the temperature reached 43.2°C after 5 min of illumination.

[0056] In order to further verify the light-stimulated drug release performance of the confined composite drug reservoir DPNP Ⅱ, 1 mL of DPNP Ⅱ was taken, the DOX concentration was 0.55 mg / mL, and the mass ratio of DOX to PDA@P(NIPAAm-co-AM) nanohydrogel was 1:1. The confined composite drug reservoir DPNP Ⅱ that formed a hydrogel by phase transition was placed in a centrifuge tube, and 3 mL of PBS solution was added at 37°C as the drug dissolution medium. At a fixed time point, 5 min of light was applied, and the light conditions were 808 nm near-infrared light with a power of 2 W. 2 mL of the medium was taken before and after illumination, and the DOX drug concentration was determined by UV-vis spectrophotometer, and an equal volume of blank medium was added.

[0057] Figure 7 Figure 2 is the drug release curve. The amount of drug released increased significantly during the light irradiation process, indicating that light can stimulate the composite drug reservoir to release the drug DOX.

[0058] This experiment verified the light-controlled anti-tumor performance of the confined light-controlled anti-tumor composite hydrogel drug reservoir through the tumor inhibition effect at the animal level. The mice used in the experiment were Balb / c female mice, and the tumor model was mouse breast cancer. The experiment used the confined light-controlled anti-tumor composite hydrogel drug reservoir DPNP Ⅰ / 10, and the DOX concentration was 15 μg / mL. Each group of materials was precisely applied to the tumor by injection. The treatment cycle lasted for 21 days. The light group was applied with 5 min of light on the 0th, 1st, 3rd, 5th, and 7th days of treatment. The light conditions were 808 nm near-infrared light with a power of 2 W.

[0059] Fig.11 The curve of the change of mouse tumor over time during the treatment cycle shows that compared with the confined light-controlled anti-tumor composite hydrogel drug reservoir without light, the light-controlled anti-tumor composite hydrogel drug reservoir significantly inhibited the growth of the tumor. Compared with the untreated group, the tumor inhibition rate reached 98%. Fig.12As shown. It can be seen that under laser irradiation, PDA nanoparticles realize photothermal energy conversion, absorb light energy and convert it into heat, increase the local temperature, further increase the gel temperature, collapse and dehydrate the gel structure, accelerate the drug outflow and diffusion rate, get rid of the rate limit of passive diffusion of drug molecules, and achieve more accurate and controllable personalized tumor treatment. Among them, NIR represents the application of light; PNP represents the composite hydrogel containing the same PDA@P (NIPAAm-co-AM) nanohydrogel concentration as the confined light-controlled anti-tumor composite hydrogel drug reservoir, but without DOX; DPN represents the drug-loaded PDA@P (NIPAAm-co-AM) nanohydrogel with the same DOX and PDA@P (NIPAAm-co-AM) nanohydrogel content as the confined light-controlled anti-tumor composite hydrogel drug reservoir, but without PLGA-PEG-PLGA Ⅱ sol.

[0060] The above embodiments describe in detail the structure, features and effects of the present invention. The above are only preferred embodiments of the present invention. Any changes made in accordance with the concept of the present invention, or modifications to equivalent embodiments with equivalent changes, which do not exceed the scope covered by the specification, should be within the protection scope of the present invention.

Claims

1. A confined light-controlled anti-tumor composite hydrogel drug reservoir, characterized in that: The invention is composed of PLGA-PEG-PLGA sol and PDA@P(NIPAAm-co-AM) nano-hydrogel loaded with DOX; the PLGA-PEG-PLGA sol and PDA@P(NIPAAm-co-AM) nano-hydrogel loaded with DOX are respectively prepared by dissolving PLGA-PEG-PLGA block copolymer and PDA@P(NIPAAm-co-AM) nano-gel loaded with DOX in water, wherein the mass ratio of PLGA-PEG-PLGA block copolymer to PDA@P(NIPAAm-co-AM) nano-gel loaded with DOX is (5-20):1; the mass ratio of DOX to PDA@P(NIPAAm-co-AM) is 1:(1-100).

2. A method for preparing the localized light-controlled anti-tumor composite hydrogel drug reservoir as claimed in claim 1, characterized in that: The method comprises the following steps: dissolving a PLGA-PEG-PLGA block copolymer in ultrapure water to obtain a PLGA-PEG-PLGA sol; dissolving a DOX-loaded PDA@P (NIPAAm-co-AM) nanohydrogel in the PLGA-PEG-PLGA sol to obtain a confined light-controlled anti-tumor composite hydrogel drug reservoir.

3. The preparation method according to claim 2, characterized in that: PLGA-PEG-PLGA block copolymer was prepared by the following method: (1) PEG, LA and GA are mixed, heated in an oil bath to 100-120° C., and stirred for 0.5-2 hours in a vacuum state to obtain a polymer fluid; the ratio of the mass of PEG to the total mass of LA and GA monomers is 1:(2-3); wherein the mass ratio of LA to GA is (3-4):1; (2) Tributyltin butenedioate C 16 H 30 O4Sn is added dropwise to the polymer fluid, heated to 120-150°C in an oil bath, and reacted for 6-24 hours under nitrogen protection. After the reaction, the PLGA-PEG-PLGA block copolymer is purified and freeze-dried to obtain the C 16 H 30 The mass ratio of O4Sn to the mass ratio of polymer is 0.1-0.5%.

4. The preparation method according to claim 3, characterized in that: The PEG is PEG 1500 or PEG 1500 and PEG 1000 in a mass ratio of (1-2):

1.

5. The preparation method according to claim 2, characterized in that: The method of the DOX-loaded PDA@P(NIPAAm-co-AM) nanohydrogel is as follows: (1) Add NIPAAm and AM to water, stir and evacuate to obtain an aqueous solution of NIPAAm and AM; (2) Add 40 parts by volume of ethanol to 90 parts by volume of ultrapure water, stir evenly at 35°C-40°C, then immediately add 3 parts by volume of ammonia water and stir evenly, add dopamine hydrochloride aqueous solution, wherein the mass volume ratio of dopamine hydrochloride to ethanol is 50 mg:4 ml, stir at 35°C-40°C and protect from light, centrifuge and wash to obtain PDA nanoparticles, and disperse the PDA nanoparticles in water to obtain a PDA solution; (3) PDA solution, NIPAAm and AM aqueous solution, SBS, APS, BIS, and SDS were mixed for reaction, and then dialyzed and freeze-dried to obtain PDA@P (NIPAAm-co-AM) nanogel; wherein the mass ratio of PDA, NIPAAm, AM, APS, SBS, SDS, and BIS was 1:180:30:2:2:40:5; (4) Dissolve the PDA@P(NIPAAm-co-AM) nanogel in an aqueous solution of DOX to obtain DOX-loaded PDA@P(NIPAAm-co-AM) nanohydrogel.

6. Use of the confined light-controlled anti-tumor composite hydrogel drug reservoir as claimed in claim 1 in the preparation of confined light-controlled anti-tumor preparations.

Citation Information

Cited By

  • Bioactive substance compounded intelligent copolymer hydrogel and dynamic drug delivery system thereof

    CN120643690A

  • Intelligent copolymer hydrogels with bioactive substance complexation and dynamic drug delivery systems

    CN120643690B